2017
DOI: 10.3892/ol.2017.5667
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference-mediated gene silencing of cyclophilin A enhances the radiosensitivity of PAa human lung adenocarcinoma cells in vitro

Abstract: Radiotherapy is currently the major therapeutic strategy for patients with lung cancer. However, radioresistance and various side effects continue to present challenging issues for this form of treatment. A recent study demonstrated that cyclophilin A (CyPA) was overexpressed in non-small cell lung cancer and, therefore, presents a novel potential therapeutic target. In addition, gene-radiotherapy is a novel method for cancer treatment. Therefore, the objective of the present study was to investigate the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The importance of cyclophilins in the G 1 /S transition has also been observed in HCC [ 20 , 21 , 22 ]. Alternatively, Jiang et al [ 40 ] reported a G 2 /M arrest due to a CypA knockdown in lung adenocarcinoma cells. Indeed, the NV651 treatment caused an early accumulation of cells in the G 2 /M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of cyclophilins in the G 1 /S transition has also been observed in HCC [ 20 , 21 , 22 ]. Alternatively, Jiang et al [ 40 ] reported a G 2 /M arrest due to a CypA knockdown in lung adenocarcinoma cells. Indeed, the NV651 treatment caused an early accumulation of cells in the G 2 /M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al recently reported that long noncoding RNA LINC00483 regulates the radiosensitivity of lung adenocarcinoma by interacting with the microRNA-144/HOXA10 signaling axis [12]. Jiang et al demonstrated that RNA interference-mediated gene silencing of cyclophilin A markedly enhanced the radiosensitivity of PAa human lung adenocarcinoma cells in vitro and induced G2/M phase cell cycle arrest [13]. Dong et al showed that speckle-type POZ protein affected DNA damage response repair kinetics, apoptosis, and cell cycle checkpoints to regulate the response of lung adenocarcinoma cells to radiation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the CypA/CD147 interaction inhibits the apoptosis of cancer cells [ 13 , 54 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. The antiapoptotic effects are associated with the upregulation of the PI3K/AKT/mTOR signaling pathway, modulation of the Bcl-2 family, and inhibition of caspase cascades [ 13 , 54 , 78 , 79 ].…”
Section: Roles Of Cypa/cd147 Interaction In Cancermentioning
confidence: 99%
“…Overexpression of CypA prevents hypoxia- and cisplatin-induced apoptosis in several cancer cell lines, including prostate cancer cells [ 56 ]. CypA is significantly upregulated after radiation therapy in lung adenocarcinoma cells, and CypA inhibition greatly increases radiosensitivity, reinforcing cell apoptosis [ 80 ]. CD147 is highly expressed in human epidermal growth factor receptor 2 (HER2)-positive breast cancer tissues, and its suppression enhances the anticancer efficacy of trastuzumab by increasing apoptosis in breast cancer cells [ 81 ].…”
Section: Roles Of Cypa/cd147 Interaction In Cancermentioning
confidence: 99%